Improvement on mechanical properties and corrosion resistance of titanium-tantalum alloys in-situ fabricated via selective laser melting - Zhao, Danlei (2020)
In this study, the role of tantalum (Ta) on the phase transformation, microstructure evolution, mechanical properties and corrosion resistance of titanium-tantalum (Ti–Ta) alloys in-situ fabricated via selective laser melting (SLM) was investigated. Ti–Ta mixed powders with different Ta ratios ranging from 0 to 25 wt % were prepared by ball milling for the SLM process. With the increase of Ta content, the SLM-processed Ti–Ta alloys exhibits the microstructure evolution from the lath α grain to acicular α' + primary cellular β grains, accompanying with the gradual suppression of martensite transformation. The β-stabilized effect of Ta promotes the formation of β (Ti, Ta) solid solution phase in the alloys. The rise of Ta addition in SLM-processed Ti–Ta alloys contributes to the improvement on the tensile strength from 641 to 1186 MPa and the microhardness from 257 to 353 HV, which results from a combined effect of grain refinement strengthening and the solid solution strengthening. The Young's modulus decreases from 115 to 89 GPa due to the increasing amount of β phase. Additionally, the corrosion resistance of the Ti–Ta alloys is enhanced with few pits on the surfaces due to the increasing amount of Ta2O5 identified through X-ray photoelectron spectroscopy. These findings provide the knowledge and boost the further understanding on the SLM-processed Ti–Ta alloys as promising candidates for biomedical application.